(untitled) (Proceedings of the World Disability & Rehabilitation Conference, 2024)
India has ratified The Universal Declaration of Human Rights (UDHR, 1948) and the United Nations Convention on Rights of Persons with Disabilities (UNCRPD, 2006). It is committed to bringing people with disabilities to the mainstream, ensuring their human rights. India has taken many steps on legislative and executive fronts to address the needs of persons with disabilities post United Nations Convention on the Rights of Persons with Disabilities (UNCRPD). Article 24 of the UNCRPD provides for accessible, quality, and inclusive education to persons with disabilities as their right so that they can develop their full potential and talent to live independently and with dignity. Education for people with disabilities has been a challenge. The Rights of Persons with Disabilities Act 2016 in India, provides for an inclusive education and accessible built environment on educational campuses. Adopting inclusive approaches is imperative to achieve the ’education for all’ goal, yet existing built environment fails to provide an inclusive and accessible built environment in India. Non- implementation of existing guidelines for accessible built infrastructure may be the cause behind this state. Architectural education institutes make a strong case to study, these institute as living labs, sensitize students about design solutions for the accessibility needs of all users in classrooms, laboratories, library, washrooms, canteen, hostels, parking facilities, etc. This paper investigates the status of accessibility in built environment in select institutes of architectural education in India by recording user response for provisions, level of service, satisfaction, etc. to appraise the on ground situation of architectural institutions. The outcome of research includes set of interventions for old and new architectural education institutions to make the built environment universally accessible.